Comparative Effectiveness of AIR (Auditory, Intellectually, Repetition) and Realistic Mathematics Education Approaches on Students’ Mathematical Reasoning Ability - Sudadio, Sudadio; Kalberg, Dave (Cahaya Ilmu Cendekia Publisher, 2026)
Purpose of the study: This study aims to compare the effectiveness of the AIR (Auditory, Intellectually, Repetition) and Realistic Mathematics Education (RME) approaches in improving students’ mathematical reasoning ability at the senior high school level. Methodology: This study employed a quantitative quasi-experimental method with a posttest-only design, using essay-based test instruments, interviews, observations, and documentation; data were analyzed using descriptive statistics, Liliefors normality test, F-test homogeneity, and independent sample t-test with statistical calculation procedures. Main Findings: The results showed a significant difference between the two approaches, where the AIR approach produced higher mean scores than the RME approach in students’ mathematical reasoning ability. Statistical testing indicated tvalue > ttable, confirming that AIR is more effective in enhancing students’ reasoning skills compared to RME. Novelty/Originality of this study: This study provides a direct comparative analysis between AIR and RME approaches within a single quasi-experimental framework, focusing specifically on mathematical reasoning ability and offering empirical evidence to support instructional decision-making in mathematics education.